Silencing of long non-coding RNA HCP5 inhibits proliferation, invasion, migration, and promotes apoptosis via regulation of miR-299-3p/SMAD5 axis in gastric cancer cells. Issue 1 (1st January 2021) - Yin, Derong; Lu, Xiaohong
ABSTRACT: Gastric cancer (GC) is a common malignant gastrointestinal tumor with high mortality. Previous study has reported that the overexpression of lncRNA HCP5 was observed in gastric cancer tissues. The purpose of this study was to investigate the molecular mechanism underlying the effect of lncRNA HCP5 on the proliferative, migratory, and invasive abilities of GC cells. The relative mRNA expression of HCP5, miR-299-3p, and SMAD5 were determined by RT-qPCR. The expressions of proteins associated with apoptosis and invasion were detected by western blot. The interaction of HCP5 with miR-299-3p and SMAD5 with miR-299-3p was confirmed by luciferase reporter assay. The cellular behaviors of AGS cells were, respectively, detected by CCK-8 assays, colony formation assays, migration and invasion assays, and flow cytometry. In our study, lncRNA HCP5 was highly expressed in GC cell lines compared with normal gastric epithelial cell. LncRNA HCP5 silencing inhibited AGS cells proliferation, migration, and invasion, while promoted cell apoptosis. Moreover, miR-299-3p downregulation could abolish the effect of HCP5 knockdown on cellular behaviors of AGS cells. Interestingly, SMAD5 is identified as the downstream target of miR-299-3p, and its expression was inhibited by miR-299-3p. More importantly, SMAD5 silencing inhibited proliferation, migration, and invasion of GC cells, and promoted cell apoptosis. In a word, lncRNA HCP5 silencing inhibits GC cell proliferation, invasion, and migration while promoting its apoptosis via regulation of miR-299-3p/SMAD5 axis. Hence, lncRNA HCP5 could be a novel and promising target for GC treatment. Graphical abstract: